Anatomical Basis and Clinical Application of the First Metatarsal Proximal Perforator‐Based Neurocutaneous Vascular Flap. Issue 5 (9th October 2019) - Hu, Deqing; Hong, Xu; Wei, Xudong; Lin, Haiqing; Zhang, Fei; Zheng, Heping; Lin, Jian
Abstract : Forefoot defects caused by accidents are very common, but their reconstruction remains a substantial challenge for plastic surgeons. The purpose of this study is to determine the anatomical structure of the first metatarsal proximal perforator‐based flap and to propose its clinical application. The study was divided into two parts: an anatomical study and a clinical application. Thirty preserved lower limbs injected with red latex were chosen for observation, and the following were recorded: the course and distribution of the medialis dorsalis pedis cutaneous nerve; the origin, course, branching and distribution of the first metatarsal proximal perforator; and the communication of the perforator and the dorsal medial vessels. Clinically, six cases of forefoot skin defects were reconstructed with the first metatarsal proximal perforator‐based neurocutaneous vascular flap. The medialis dorsalis pedis cutaneous nerve mainly arose from the medial branch of the superficial peroneal nerve and proceeded forward for a distance of 2.5 ± 0.4 cm under the surface of the inferior extensor retinaculum; then, the nerve divided into the medial dorsal branch and the first and second dorsal metatarsal branches. The first metatarsal proximal perforator‐based neurocutaneous vessels were multisegmented and multisourced, and the first branch was closely related to the operative procedure. In terms of the clinical application, all flaps of the six cases survived completely with good appearance, texture and elasticity. The first metatarsal proximal perforators present as constant. The first metatarsal proximal perforator‐based neurocutaneous vascular flap may become a useful supplemental material for the reconstruction of forefoot defects. Clin. Anat., 33:653–660, 2020. © 2019 Wiley Periodicals, Inc.